Analisis Kualitas Pelayanan Publik Di Unit Pelaksana Teknis Pengujian Kendaraan Bermotor Dinas Perhubungan Kabupaten Padang Pariaman - Indah Rohani; Roni Ekha Putra (Jurnal Administrasi Publik dan Pemerintahan, 2023)
This thesis is a research that aims to describe and analyze the quality of public services in the Technical Implementation Unit of Motor Vehicle Testing of the Padang Pariaman Regency Transportation Office. The research refers to Sinambela's theory which states that the quality of excellent service is reflected in: Transparency, Accountability, Conditional, Participative, Equal Rights, Balance of Rights and Obligations. Then this research uses a qualitative approach with descriptive research methods. Data collection techniques are carried out by interviews, documentation, and observation. Furthermore, the informant selection technique in this study is a purposive sampling technique and the validity of the data is carried out by source triangulation techniques. The results showed that the quality of motor vehicle testing services at the Technical Implementation Unit of Motor Vehicle Testing of the Padang Pariaman Regency Transportation Office has run quite well although in some indicators there are still not optimal such as transparency indicators, namely the absence of socialization about services to the community